Recent advances in transition metal nitrides for hydrogen electrocatalysis in alkaline media: From catalyst design to application - Tang, Siyuan; Zhang, Zhipeng; Xiang, Jun; Yang, Xinchun; Shen, Xiangqian; Song, Fuzhan (Frontiers in Chemistry, 2022)
Hydrogen (H2) has been considered an ideal alternative energy source for solving energy supply security and greenhouse gas reduction. Although platinum group metal (PGM) catalysts have excellent performance in hydrogen electrocatalysis, their scarcity and high cost limit their industrial application. Therefore, it is necessary to develop low-cost and efficient non-PGM catalysts. Transition metal nitrides (TMNs) have attracted much attention because of their excellent catalytic performance in hydrogen electrochemistry, including hydrogen evolution reaction (HER)/hydrogen oxidation reaction (HOR). In this paper, we review and discuss the mechanism of HER/HOR in alkaline media. We compare and evaluate electrocatalytic performance for the HER/HOR TMN catalysts recently reported. Finally, we propose the prospects and research trends in sustainable alkaline hydrogen electrocatalysis.